IMAGE PROCESSING APPARATUS, IMAGE PROCESSING METHOD AND PROGRAM - KOBAYASHI NORIHIKO (2021)
To make an image processing apparatus perform a start-up operation according to a type of start-up recognized by a user.SOLUTION: A client machine 120 includes return from a sleep state, return from a power-saving state that enables quick start-up and start-up with normal power-on as start-up operations. An event recovery unit 510 has a function of executing start-up time collection processing being processing of collecting information to be notified at the start-up. An event sending unit 530 has a function of notifying of information collected in the start-up time collection processing via a network. The event recovery unit 510 executes the start-up time collection processing in a case of returning from the power-saving state with the quick start-up and a case of starting up with the normal power-on, but does not execute the start-up time collection processing in a case of returning from the sleep state.SELECTED DRAWING: Figure 5 【課題】画像処理装置が、ユーザが認識した起動の種類に併せた起動動作を行うようにする。【解決手段】クライアント機１２０は、起動動作として、スリープ状態からの復帰、高速起動が可能な省電力状態からの復帰、通常の電源オンによる起動を含む。イベント回収部５１０は、起動時に、通知すべき情報を収集する処理である起動時収集処理を実行する機能を有する。イベント送付部５３０は、起動時収集処理で収集された情報をネットワークを介して通知する機能を有する。イベント回収部５１０は、高速起動による省電力状態から復帰する際や通常の電源オンによる起動の際には起動時収集処理を実行するが、スリープ状態から復帰する際には起動時収集処理を実行しない。【選択図】図５